Produtividade e qualidade de frutas de clones de morangueiro em sistema fechado de cultivo sem solo - Lopes, Gabriel de Araujo (2023)
Strawberry is one of the most appreciated fruits by the world population, due to its flavor, color and aroma. In Brazil, the crop has been expanding, in area and production, and plays an important socioeconomic role, however the main cultivars used are developed in other countries. To gain access, producers depend on importing bare-root seedlings, which is a legal requirement and has high mortality rates after transplantation. This work aimed to compare the productivity and fruit quality of four strawberry clones in successive harvests. The experiments were carried out in a completely randomized design in two locations in the municipality of Santa Maria - RS, in the years 2021 and 2022 on two planting dates in each year. The first experiment was carried out on the to validate the yield and fruit quality of three strawberry clones in a commercial field. The other three experiments were carried out in the experimental area of the Departamento de Fitotecnia of the Universidade Federal de Santa Maria. The data were submitted to analysis of variance and the means of the clones were compared by the Scott- Knott test, at 5% probability of error. In these studies, the number and fresh mass of the fruits, the total soluble solids content, the titratable acidity, the pH, the ratio of total soluble solids and the titratable acidity were evaluated and the color was determined by reflectance by the CIELAB system. The quantitative data were applied in a sigmoid function of a logistic equation, with the coefficients of the formula the productive potential, the inflection point and the growth rate of the number or fresh mass of fruits of each clone were assigned. This information can help optimize current strawberry management practices to increase resource efficiency.